The Role of Geographic Information System in Environmental Planning and Management in Oman - Ruheili, Amna, M., Al; Wardy, Malik Al (International Journal of Membrane Science and Technology, 2023)
The use of Geographic Information Systems (GIS) has grown to cover various disciplines. The ability to use big data and geoprocessing tools allowed many sectors to use spatial data analysis and modeling for more effective decision-making and increased productivity. The use of GIS has become even more vital in the field of environmental planning and management, where incorporating environmental information contributes significantly to sustainable development. In addition, the ability to use spatial modeling at small-scale local or large-scale regional levels will broaden the knowledge of the direct and indirect impacts of development projects on the environment. This paper assesses the role played by GIS in Oman for generating information to gain insight into the many environmental challenges faced by the country toward more sustainable development. It provides an overview of what has been achieved, the approaches taken, and the way forward.